IMPROVING THE EFFICIENCY OF DIGITAL MARKETING OF ORGANIC PLANT PRODUCTS - Kupalova, Halyna; 1goncharenkо nataliia (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2021)
The directions of increase of efficiency of use of digital marketing of organic crop production were investigated in the article. The urgency of the study is due to the need to reorient markets by increasing the share of products sold on national and local markets, optimizing logistics chains, disseminating information about domestic producers and brands, range of organic products via the Internet and other electronic networks. It was noted that the global and domestic trends are the growth of e-commerce and sales of organic products using digital marketing tools. Adaptation to trade and logistics restrictions caused, in particular by quarantine restrictions, forces companies to increase marketing activity on the Internet, to use offline and online tools to promote goods and services. Trends in the use of digital marketing tools by producers of organic crop products in Ukraine were analyzed. It was established that most often domestic companies use Internet sites, social networks, development and promotion of trademarks to promote organic products. Improving the effectiveness of digital marketing of organic crop products is possible through the optimal combination of different tools that take into account the target audience, the specifics of the finished product, the marketing strategy of the enterprise. According to the results of factor analysis, the effectiveness of the promotion of organic crop products is influenced by the intensity of visits to the company’s website, the frequency of orders in the CRM system and the completeness of their processing, the prevalence of social networks. The advantages and disadvantages of digital marketing tools for promoting organic crop products, namely SEO, CRM-systems, social networks. The structural and logical model of digital marketing of organic crop products was proposed, consisting of three blocks: initial, promoting and activating. Each of them includes a set of tools that will increase sales at optimal costs. When conquering market niches and strengthening market positions, it is proposed to develop and promote a specialized site. This will ensure active communication through social networks. With the development of the organic direction of business, the gradual expansion of the range and increase market share is relevant to the use of SEO, CRM-systems, cloud computing. The application of the proposed structural and logical model of digital marketing of organic crop products will help increase sales, develop a strategy to promote products, optimize advertising costs, stimulate the promotion of environmentally friendly products.